Inferior Alveolar Nerve Lateralization and Implant Placement in Atrophic Posterior Mandible - Suzuki, Dalton; Farnezi Bassi, Ana Paula [UNESP]; Lee, Hyung Joo; Alcantara, Paola Rebelatto; de Sartori, Ivete Mattias; Luvizuto, Eloa R. [UNESP]; Faco, Eduardo F. S. [UNESP]; Faot, Fernanda (Lippincott Williams & Wilkins, 2012)
The aims of this article were to describe the surgical technique of the inferior alveolar nerve lateralization followed by implant installation by means of a clinical report and also to discuss the importance of an adequate surgical and prosthetic planning for atrophic posterior mandible rehabilitation.
Keywords: Inferior alveolar nerve lateralization; bone; implants; mandible